Os estádios e as metrópoles contemporâneas: a produção arquitetônica no Brasil entre 2010 e 2016 - Pelakauskas, Thiago Vidal (2019)
This dissertation addresses the contemporary scenario in which metropolises around the globe compete with each other for the right to host the so-called megaevents – international sports competitions, great spectacles and musical shows etc – and whose purpose is to study the stadiums - a specific typology of edification with the main function to accommodate these events - as well as the relationship of each stadium with the city in which it is inserted. These events are used as inducers of urban interventions called "necessary", as their promoters propagate, since their realization can enhance the symbolic image of the metropolis in the international environment, besides generating an effective movement of capital, activating productive sectors as civil construction, tourism, as well as infrastructural improvements in airports and highways, among others, thus generating supposed "legacies" for the city that hosts the megaevent. Therefore, the main issue is to discusse the impacts of these urban and architectural interventions, trying to identify what their main characteristics would be. Thus, the work is structured in six parts: 1) definition of methodological procedures; 2) the history of soccer in Brazil and the consequent construction of the first stadiums, with emphasis on the Soccer World Cup, in 1950, and the Pan American Games, in 1963, as well as an interlude, between 1964 and 1999, when there was an intensive production of emblematic stadiums; 3) an analysis of the 2007 Pan-American games in Rio de Janeiro, and the São Paulo city bid project for the 2012 Olympic Games; 4) the competition between cities and stadiums built or renovated to host the 2014 FIFA World Cup Brazil, with a more detailed study of the stadiums of S. Corinthians and S. E. Palmeiras in the city of São Paulo; 5) the 2016 Olympic and Paralympic Games in the city of Rio de Janeiro, with internal disputes at the city, observing the dichotomy between projects and buildings; 6) an appendix, containing complementary analyzes of the main stadiums cited in this work.